The Relationship Between Social Support and Self-esteem in People with HIV/AIDS - Marlina Marlina; Yola Yolanda (Frontiers on Healthcare Research)
Background: People with HIV/AIDS experience both physical and emotional challenges. The existence of stigma and discrimination significantly affects their self-esteem. However, limited research has explored the direct relationship between social support and self-esteem within healthcare settings, particularly in Indonesia. Understanding this relationship is crucial for developing effective psychosocial interventions. This research aims to determine the relationship between social support and self-esteem in people with HIV/AIDS at VCT Polyclinic RSUP Dr. M. Djamil Padang